1976
DOI: 10.1159/000122468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drugs That Modify Brain Biogenic Amine Concentrations on Thyroid Activation Induced by Exposure to Cold

Abstract: L-Dihydroxyphenylalanine (L-DOPA)significantly inhibited intrathyroidal colloid droplet formation induced by exposure to cold in the rat. Diethyldithiocarbamate (DDC) also inhibited colloid droplet formation in response to cold. The combined administration of L-DOPA and DDC produced an additive inhibition of the thyroidal endocytotic response to exposure to cold. Pretreatment with chlorpromazine (CPZ) ameliorated the inhibitory effect of (L-DOPA)DL-alpha-methyl-p-tyrosine (α-MT) also significantly depressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…There are many reports concerning the effects of amines, peptides and prostaglan dins (PGs) on thyrotoropin (TSH) secretion [1,2,4,7,9,10,12,13,19,21,23,[26][27][28][29][30][31][32][33], Substance P (SP), PG D2 and angiotensin II are found in the hypothalamus in rats [3,8,10,13,15], suggesting that they may affect thyrotropin-releasing hormone (TRH) and TSH secretion. A few studies have been made on the role of the cholinergic system in TSH secretion [1,10,12,21], Therefore, the authors investigated the effects of SP, angio tensin II, PG D2 and oxotremorine, a cholin ergic agonist, on TRH and TSH release in rats and have studied the possible mecha nism by which these substance exert their effect on TRH and TSH release.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports concerning the effects of amines, peptides and prostaglan dins (PGs) on thyrotoropin (TSH) secretion [1,2,4,7,9,10,12,13,19,21,23,[26][27][28][29][30][31][32][33], Substance P (SP), PG D2 and angiotensin II are found in the hypothalamus in rats [3,8,10,13,15], suggesting that they may affect thyrotropin-releasing hormone (TRH) and TSH secretion. A few studies have been made on the role of the cholinergic system in TSH secretion [1,10,12,21], Therefore, the authors investigated the effects of SP, angio tensin II, PG D2 and oxotremorine, a cholin ergic agonist, on TRH and TSH release in rats and have studied the possible mecha nism by which these substance exert their effect on TRH and TSH release.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of TSH release by 5-HT has been suggested in studies em ploying intraventricular injection of 5-HT [17,18,39] and intraventricular and parenteral administration of the 5-HT precursor 5-hydroxytryptophan (5-HTP) [5,32] and the 5-HT synthesis inhibiting p-chlorophenylalanine [5,33], Con versely, inhibition of TSH release by 5-HT has been sugges ted in studies employing inirahypothalamic implants or in traventricular injection of 5-HT [15,23] and intraventricular or parenteral administration of the 5-HT agonist quipazine [19], the 5-HT-releasing ¿/-fenfluramine [8,9], the 5-HT pre cursor tryptophan [22,24,25], and p-chlorophenylalanine [31]. Further, studies employing 5-HTP suggest that 5-HT inhibits cold-induced activation of TSH [27,37].…”
mentioning
confidence: 99%
“…Joseph-Bravo et al [4] reported that HA stimulated TRH release from rat mediobasal hypothalamus in vitro. Onaya and Hashizume [13] reported that bromoserine phosphate, a depletor of HA, inhibited increase in colloid droplet forma tion of mice thyroid under cold exposure. The present findings are in agreement with a report by Tuominen et al [ 15] and contrast to the reports of Joseph-Bravo et al [4] and Onaya and Hashizume [13].…”
Section: Discussionmentioning
confidence: 99%
“…Onaya and Hashizume [13] reported that bromoserine phosphate, a depletor of HA, inhibited increase in colloid droplet forma tion of mice thyroid under cold exposure. The present findings are in agreement with a report by Tuominen et al [ 15] and contrast to the reports of Joseph-Bravo et al [4] and Onaya and Hashizume [13]. The reason for this discrepancy is unclear, but it may be attributed to the differences in experimental conditions, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation